2019
DOI: 10.7554/elife.47544
|View full text |Cite
|
Sign up to set email alerts
|

Distinct mechanisms of microRNA sorting into cancer cell-derived extracellular vesicle subtypes

Abstract: Extracellular vesicles (EVs) encompass a variety of vesicles secreted into the extracellular space. EVs have been implicated in promoting tumor metastasis, but the molecular composition of tumor-derived EV sub-types and the mechanisms by which molecules are sorted into EVs remain mostly unknown. We report the separation of two small EV sub-populations from a metastatic breast cancer cell line, with biochemical features consistent with different sub-cellular origins. These EV sub-types use different mechanisms … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
162
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(187 citation statements)
references
References 87 publications
10
162
2
Order By: Relevance
“…It has been reported that cancer cell-derived exosomes encapsulate Dicer and AGO2 together with pre-miRNAs and that at least some degree of cell-independent miRNA biogenesis occurs in the extracellular space 70 . This finding is still controversial as others have not detected AGO2 or Dicer in the ultracentrifugation pellets of cell-conditioned medium 26 or in low-density fractions enriched in EVs 67,71,72 . In summary, although some degree of intravesicular RNA processing is feasible, the nonvesicular extracellular fraction is intrinsically and highly dynamic while EVs tend to confer an RNase-protecting environment where less stable RNAs can persist ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…It has been reported that cancer cell-derived exosomes encapsulate Dicer and AGO2 together with pre-miRNAs and that at least some degree of cell-independent miRNA biogenesis occurs in the extracellular space 70 . This finding is still controversial as others have not detected AGO2 or Dicer in the ultracentrifugation pellets of cell-conditioned medium 26 or in low-density fractions enriched in EVs 67,71,72 . In summary, although some degree of intravesicular RNA processing is feasible, the nonvesicular extracellular fraction is intrinsically and highly dynamic while EVs tend to confer an RNase-protecting environment where less stable RNAs can persist ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 95%
“…For instance, Bioanalyzer’s peaks corresponding to intact 18S and 28S rRNAs have been identified in purified EVs 26,6164 , while full-length YRNAs and other ncRNAs have been identified by sequencing, RT-qPCR and/or Northern blot 31,65 . The use of thermostable group II intron reverse transcriptases (TGIRT-seq) has allowed the identification of full-length tRNAs in EVs, which greatly outnumber tRNA-derived fragments 53,66,67 . Our results are consistent with these reports, and clearly show the presence of tRNAs and 7SL RNAs in EVs purified by buoyant density flotation in linear iodixanol gradients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current accumulated knowledge about the mechanisms of ncRNAs sorting into secretory vesicles is focused on miRNAs in human and mammalian cells. Experimental evidence showed that the miRNA sorting into exosomes and other vesicles is mediated by RNA-binding and cytoskeleton proteins, following patterns that appear to be cell specific [40][41][42]. Interestingly, in human cells, the external perturbation of the expression of individual miRNAs or their cognate targets promotes bidirectional miRNA relocation from the cytoplasm to multivesicular bodies, controlling the miRNA sorting to exosomes [43].…”
Section: Conveyors For Ncrna Transport Between Cellsmentioning
confidence: 99%
“…These blood-based miRNAs are referred to as "circulating miRNAs". The secretion of miRNAs seems to be a controlled, active, and specific process as they are selectively included in EVs [6,11,12]. These observations indicate that circulating miRNAs may reflect physiological and pathological processes occurring in different cells and tissues, and so might be valuable blood-based biomarkers of various diseases.…”
Section: Introductionmentioning
confidence: 98%